A Future Study on the Adoption of Hologram Traffic Light for Reducing Accidents in Malaysia - Rafiuddin Afkari, Zulfana Lidinillah; Siti Aisyah Salim, (Research in Management of Technology and Business, 2023)
Three-dimensional hologram is a system that consists of a virtualholographic wall that can reduce reckless drivers at traffic lights. The concept isbased on a laser projector that only shows images of moving pedestrians, visiblewith a light red-light laser to drivers in front of it. Even with regular traffic lights,it is impossible to reduce traffic accidents. The current study is also focused onroad users how to reduce accident, and there is still a lack of research on thefollowing perspectives of hologram traffic lights in Malaysia. Due to theincreasing number of vehicles on the highway, the function of traffic lights iscritical, and their presence isrequired to maintain traffic order. When driving, thedriver must pay attention to the color of the traffic lights. Hence, this researchaims to identify the level of road users to maintain the safety of pedestrians andvehicles if we use hologram traffic lights in Malaysia. Furthermore, holographictraffic lights will aid communication between vehicles and pedestrians in high-risk regions. The sample was gathered using a quantitative research method thatincluded a self-administered questionnaire and an internet survey. All of thegathered data was examined using the Statistical Package for Social Science(SPSS) to create quantitative results in frequency, percentage, mean and standarddeviation. These study research ways to decrease accidents by employinghologram traffic lights for drivers.